Measures of body adiposity and visceral adiposity index as predictors of metabolic syndrome among Thai women with PCOS - Kitirat Techatraisak (2018)
© 2015 Taylor & Francis. Aim: To evaluate the relationship between measures of body adiposity and visceral adiposity index (VAI) and risk of metabolic syndrome (MS) and to identify the optimal cut-off points of each measurement in Thai polycystic ovary syndrome (PCOS).Methods: A cross-sectional study was completed physical examination, fasting plasma glucose, lipid profiles of 399 PCOS and 42 age-matched normal controls. Body mass index (BMI), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR) and VAI were calculated. Associations between different measures and MS were evaluated and the receiver-operating characteristic (ROC) curve was performed to determine appropriate cut-off points for identifying MS.Results: Percentage of MS in PCOS was 24.6%, whereas none MS in controls. Previously recommended cut-off values for body adiposity and VAI were significantly associated with MS. ROC curve analysis of the only PCOS showed newly obtained optimal cut-off points for BMI and VAI of ≥28 kg/m2 (AUC = 0.90) and >5.6 (AUC = 0.94), respectively. Values found to be more accurate than the original ones. VAI was the best predictor, followed by BMI and WHtR.Conclusion: All body adiposity and VAI parameters can predict the risk of MS. Optimal values for Thai PCOS were ≥28 kg/m2 for BMI, ≥0.85 for WHR, ≥0.5 for WHtR and >5.6 for VAI.